A scoping review: Developing a collaborative learning culture for ESL learners - Ravana, V.; Yue, W. S.; Palpanadan, S. T.; Noranai, Z.; Harun, H.; Ibrahim, M. Y.; Bosro, M. Z. M. (2024)
This review investigates recent studies from the years 2005-2020 with empirical data on how online communication tools have been used to develop a collaborative learning culture for English as a Second Language (ESL) and English as a Foreign Language (EFL) learners in various countries. Some online communication tools that fall under the categories of social networking sites such as Facebook, Twitter and Ning, blogging sites such as Blogger and WordPress and, instant messaging applications such as WhatsApp, Skype and Yahoo! Messenger have been identified as the most commonly used tools in promoting collaborative e-learning among language learners. Based on the thematic analysis conducted on the articles, collaborative e-learning activities that are properly planned and executed are found to be able to increase learner autonomy, improve student engagement among one another, boost confidence and lower anxiety among students and promote optimization of synchronous and asynchronous combination tools in learning. Directions for further inquiry have been outlined in terms of teacher readiness to shift role into a facilitator or moderator and, proper planning of online assessment and evaluation methods